2005
DOI: 10.1002/art.20745
|View full text |Cite
|
Sign up to set email alerts
|

Increase in activated CD8+ T lymphocytes expressing perforin and granzyme B correlates with disease activity in patients with systemic lupus erythematosus

Abstract: Objective. Cytotoxic T lymphocyte-mediated killing using granzyme B has recently been proposed to be a preferential and selective source of autoantigens in systemic autoimmune diseases, including systemic lupus erythematosus (SLE), while other reports have indicated that cytolytic activity in SLE patients was decreased. The aim of this study was to examine the phenotypic and functional status of the CD8؉ T cells in SLE patients.Methods. Phenotype analysis of CD8؉ T cells was carried out using flow cytometry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
165
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 225 publications
(185 citation statements)
references
References 31 publications
(37 reference statements)
10
165
2
8
Order By: Relevance
“…We have reported that dendritic cells derived from normal monocytes cultured with SLE sera or IFN␣ had the unique capacity to stimulate CD8ϩ T lymphocytes and to skew their phenotype toward cytotoxic effector cells (11). Consistent with this observation, Peterson et al (29) found that renal glomeruli from patients with lupus nephritis were characterized by high expression of genes with promoters containing type I IFN response elements.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…We have reported that dendritic cells derived from normal monocytes cultured with SLE sera or IFN␣ had the unique capacity to stimulate CD8ϩ T lymphocytes and to skew their phenotype toward cytotoxic effector cells (11). Consistent with this observation, Peterson et al (29) found that renal glomeruli from patients with lupus nephritis were characterized by high expression of genes with promoters containing type I IFN response elements.…”
Section: Discussionmentioning
confidence: 57%
“…We demonstrated that this T lymphocyte subset activation was mainly type I IFN-dependent and that these cells were able to produce large amounts of nuclear-containing bodies in vitro (11). Even though the increase in this cell population was correlated with disease activity, data are still lacking for their direct involvement in tissue damage.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations